ASUHAN KEBIDANAN IBU BERSALIN DAN BBL NORMAL DI RUANG VK KLINIK UTAMA NILAM SARI TEMBILAHAN TAHUN 2019 - Jamilah; Madinah (STIKES HUSADA GEMILANG, 2021)
The number of maternal deaths In Indragiri Hilir Regency in 2018 was 9 people and neonates 21 people. The high death rate of mothers and neonates is expected to be able to carry out their duties professionally and qualifiedly. The purpose of this care is able to provide comprehensive midwifery care services to maternity mothers and newborns at Mrs